Dose–response associations between physical activity and sedentary time with functional disability in older adults with or without frailty: a prospective cohort study - Seino, Satoshi; Abe, Takumi; Nofuji, Yu; Hata, Toshiki; Shinkai, Shoji; Kitamura, Akihiko; Fujiwara, Yoshinori (Frontiers in Public Health, 2024)
Purpose Evidence regarding the dose–response curve shapes of physical activity (PA) and sedentary time (ST) in older adults with functional disability (FD) is extremely limited. Moreover, these associations may differ depending on with/without frailty. We examined the dose–response associations between moderate-to-vigorous PA (MVPA) and ST with FD among older adults with/without frailty. Methods We included 7,480 initially nondisabled adults (3,795 men and 3,685 women) aged 65–84 years in Ota City, Tokyo, Japan. MVPA and ST were evaluated using the International Physical Activity Questionnaire-Short Form. FD was prospectively identified using a nationally unified database of the long-term care insurance system. Frailty was determined using Check-List 15, validated against Fried’s frailty criteria. Multivariate-adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) of MVPA and ST for FD were calculated, and dose–response curves were examined using restricted cubic splines. Results During 3.6 years of follow-up, 1,001 (13.4%) participants had FD. Among all participants, compared with no MVPA, the HRs for FD reduced linearly up to approximately 2000 metabolic equivalents (METs)■min/week of MVPA, and the lowest HR (HR: 0.61, 95% CI: 0.51–0.74) was reached at around 3,000–4,000 METs■min/week. Although the shape of this association was consistent regardless of with/without frailty, the magnitude of the association tended to be stronger in frail older adults than in non-frail older adults. Compared with those for the median (300 min/day) of ST, the HRs for FD increased linearly as ST reached approximately 600 min/day or more, independent of MVPA, with a maximum HR of 1.31 (95% CI: 1.01–1.71) for 1,080 min/day among all participants. This association was more pronounced among non-frail older adults but not statistically significant among frail older adults. Conclusion Higher MVPA levels consistently reduced the incidence of FD regardless of frailty in a significant inverse nonlinear dose–response manner. A significant positive nonlinear dose–response association between ST and FD risk was identified among non-frail older adults but not among frail older adults. Increasing MVPA and reducing prolonged ST are important for preventing FD among non-frail older adults. However, reducing ST alone may be insufficient; increasing MVPA, even if by only small increments, is highly recommended for frail older adults.